Hotspot Distribution Pattern As an Indicator of Forest and Land Fires in West Aceh District - Bambang Hero Saharjo; Muhammad Rizki Ananda Nasution (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
One of the provinces in Indonesia that experiences forest and land fires every year is Aceh Province. Aceh Barat District is one of the districts in Aceh Province where forest and land fires occur every dry season. Forest and land fires prevention can be done by utilizing hotspot data for analysis using geographic information systems (GIS). This research aims to analyze the distribution of hotspots and the correlation between rainfall and hotspots as an indicator of the occurrence of forest and land fires in West Aceh Regency in 2014-2019. This research uses MODIS LAPAN hotspots data, land cover distribution maps, peat land distribution maps, administrative maps and rainfall data from BMKG. The correlation between rainfall data and hotspot data was carried out by the bivariate pearson correlation test. The resuls of the research found that there were 576 hotspots in West Aceh Regency from 2014-2019. The district with the highest number of hotspots is in Samatiga District, namely 131 hotspots. The most dominant hotspots are in the peatland cover, as much as 64% and in the swamp scrub land cover area with 126 hotspots. Correlation test results show that rainfall with a negative correlation, that the decrease in rainfall is followed by an increase in hotspots. Keywords: Aceh Barat, fires, GIS, hotspot, rainfall